Compositions comprising an acrylic monomer having a carboxylic acid group, an acrylic monomer having a hydroxyl group, an alkyl (meth)acrylate monomer, and a crosslinker, and related articles and methods
Patent Information
- Application Number
- CN202180085563.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-17
- Filing Date
- 2021-12-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2041-12-17
Smart Images

Figure CN116981705B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority to U.S. Provisional Application No. 63 / 127,065, filed December 17, 2020, the disclosure of which is incorporated herein by reference in its entirety. Background Technology
[0003] Adhesives are known to be used to bond one substrate to another, such as bonding metal to metal, metal to plastic, plastic to plastic, and glass to glass. Structural adhesives are an attractive alternative to mechanical joining methods such as riveting or spot welding because they distribute load stress over a larger area rather than concentrating it at a few points. Structural adhesives also produce cleaner and quieter products because they dampen vibrations and reduce noise. Furthermore, structural adhesives can be used to bond a variety of materials, sometimes without requiring extensive surface preparation.
[0004] Crosslinking agents that can be used in certain adhesive compositions are described in U.S. Patent Nos. 4,605,712 (Mueller et al.) and 4,447,493 (Driscoll et al.), and U.S. Patent Application Publication Nos. 2016 / 0137893 (Sherman et al.), 2012 / 0139138 (Samuel et al.), 2017 / 0135911 (Craig et al.), and 2020 / 017720 (Liu et al.). Certain acrylic adhesives reported to have high strength or high glass transition temperatures are described in International Patent Application Publication No. WO2019 / 012088 (Hajji et al.), Japanese Patent Application JP2016155892 published September 1, 2016, and Chinese Patent Application CN104449418 published March 25, 2015. Summary of the Invention
[0005] This disclosure provides a composition that can be used, for example, as a sealant or adhesive (e.g., a structural adhesive). In one aspect, this disclosure provides a composition comprising at least one of an acrylic monomer having a carboxylic acid group, an acrylic monomer having a hydroxyl group, an alkyl acrylate, or an alkyl methacrylate, and a compound consisting of a divalent segment L and at least two X groups. The divalent segment L is represented by the following formula:
[0006] L.
[0007] Each divalent segment L is directly bonded to: i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group. ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or iii) A secondary N atom, which is directly bonded to another divalent segment L or X group; and a tertiary N atom, which is directly bonded to p other divalent segments L and (2-p) X groups, where p is 0, 1 or 2.
[0008] In the bivalent chain segment L, each R 1 Independently represents an alkylene group having 1 to 4 carbon atoms, provided that R 1 At least some of the groups are -CH2-CH2-CH2-CH2-. Each n independently represents a positive integer, and each X group is independently represented by the following formula: CH2=C(R)-C(O)-OVWC(O)-, Each R is independently hydrogen or methyl, and each W is independently O, S, or NR. 2 , where R 2 The group is hydrogen or an alkyl group having at most four carbon atoms, and each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group. Based on the total weight of the acrylic functional compound in the composition, the acrylic monomer having a carboxylic acid group is present in an amount of at least 1% by weight and less than 20% by weight. Based on the total weight of the acrylic functional compound in the composition, the compound consisting of a divalent segment L and at least two X groups is present in an amount of 20% to 35% by weight.
[0009] In some embodiments, the acrylic monomer containing a hydroxyl group is present in an amount of at least 5% by weight and at most 25% by weight, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the composition comprises methyl methacrylate in an amount of at least 20% by weight and at most 50% by weight, based on the total weight of the acrylic functional compounds in the composition.
[0010] In another aspect, this disclosure provides an adhesive comprising the composition disclosed herein, which is at least partially cured with a free radical initiator.
[0011] In another aspect, this disclosure provides an article of manufacture that is bonded using the composition disclosed herein, which is at least partially cured with a free radical initiator.
[0012] In another aspect, this disclosure provides a method for manufacturing an adhesive article. The method includes combining the composition disclosed herein with a free radical initiator to provide an adhesive composition; applying the adhesive composition to at least one of a first substrate or a second substrate; adhering the first substrate and the second substrate using the adhesive composition; and allowing the adhesive composition to at least partially cure to prepare an adhesive article.
[0013] As used in this article: The term "alkyl group" and the prefix "alkane" have only C-C and CH bonds and include straight-chain, branched, and cyclic groups. In some embodiments, unless otherwise specified, the alkyl group has up to 30 carbons (in some embodiments, up to 20, 15, 12, 10, 8, 7, 6, or 5 carbons). The cyclic group can be monocyclic or polycyclic and, in some embodiments, has 3 to 10 cyclic carbon atoms and other alkyl substituents; The term "acrylic" refers to acrylic and methacrylic polymers, oligomers, and monomers. The term "direct bond to" refers to bonding via a single covalent bond; The term "radical polymerization" refers to radical homopolymerization and / or radical copolymerization (i.e., with different monomers / oligomers). The term "(meth)acryl" refers to acryl (also known in the art as acryloyl and acrylyl) and / or methacryl (also known in the art as methacryloyl and methacrylyl); The term "secondary nitrogen" refers to a neutral nitrogen atom covalently bonded to H and two carbon atoms; and The term "tertiary nitrogen" refers to a neutral nitrogen atom covalently bonded to three carbon atoms.
[0014] Terms such as “a,” “an,” “the,” and “the” are not intended to refer to a single entity, but rather to encompass a general category of specific examples that can be used to illustrate the point. The terms “a,” “an,” “the,” and “the” are used interchangeably with the term “at least one (kind).”
[0015] The phrase "including at least one of..." followed by a list means including any item in the list or any combination of two or more items in the list.
[0016] The terms "cured" and "curable" refer to polymer chains linked together by covalent chemical bonds, typically through crosslinking molecules or groups, to form a network polymer. Therefore, in this disclosure, the terms "cured" and "crosslinked" are used interchangeably. Cured or crosslinked polymers are typically characterized by insolubility, but can be swollen in the presence of a suitable solvent.
[0017] Unless otherwise specified, all numerical ranges include their endpoints and the non-integer values between them (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0018] The features and advantages of this disclosure will be further understood upon consideration of the specific embodiments and the appended claims. Detailed Implementation
[0019] A high glass transition temperature is often desirable in adhesives, for example, to allow the adhesive to maintain consistent performance at high temperatures. A common strategy to increase the final glass transition temperature (Tg) of cured epoxy or polyurethane structural adhesives is to apply external heat during the curing process. For example, when 3M's DP420 (a 2-part epoxy adhesive) cures at room temperature for several days, the cured adhesive's Tg only reaches about 44°C, as measured by dynamic mechanical analysis using the methods described in the examples below. If the adhesive is heat-cured at approximately 138°C for several hours, the Tg increases to 80°C. However, low-temperature curing has become increasingly desirable, particularly in applications involving electronic components and plastic bonding, where bonding of heat-sensitive substrates occurs. Low-temperature curing also reduces thermal stress due to CTE (coefficient of thermal expansion) mismatch.
[0020] While known structural adhesives can exhibit good high-temperature performance and durability, the rigid bond they produce after curing can lead to poor impact resistance and subsequent bond failure in the bonded components. Furthermore, adhesives with rigid bonds exhibit high and uneven stress distribution throughout the bond, with stress at the bond edges typically higher than in the middle. The high stress in rigid structural adhesives can cause undesirable deformation of the bonded material (i.e., bond penetration), which can be visually observed, especially when bonding large components such as, for example, automotive panels.
[0021] This disclosure provides compositions that provide adhesives with glass transition temperatures in the range of 90°C to 130°C or 100°C to 120°C when cured at room temperature, and adhesive structures that exhibit good adhesion to a variety of substrates even when the substrate has not undergone surface treatment (e.g., corona, flame, abrasion) prior to bonding. Typically, the compositions provide adhesives with available elongation, which improves impact resistance and reduces stress in the adhesive layer. In some embodiments, the compositions of this disclosure provide adhesives with excellent water and moisture resistance.
[0022] The compositions disclosed herein comprise compounds that can be used, for example, as crosslinking agents. The compound comprises at least two X groups and includes a divalent segment L represented by the following formula:
[0023] L.
[0024] Each bivalent segment L is directly bonded to: (The following is a list of individual covalent bonds shown at each end of the bivalent segment.) i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group. ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or iii) A secondary N atom, which is directly bonded to another divalent segment L or X group; and a tertiary N atom, which is directly bonded to p other divalent segments L and (2-p) X groups, where p is 0, 1 or 2.
[0025] Each R in the bivalent chain segment L 1 Independently represents an alkylene group having 1 to 4 carbon atoms, provided that R 1 At least some of the groups are -CH2-CH2-CH2-CH2-. In some embodiments, at least 50%, 60%, 70%, 80%, 90%, or 95% of the R groups are present. 1 The radical is -CH2-CH2-CH2-CH2-. Other available R radicals... 1 The groups include -CH2-, -CH2-CH2-, -CH2-CH2-CH2-, –CH(CH3)CH2-, –CH2CH(CH3)-, –CH(CH2CH3)CH2-, –CH2(CH2CH3)CH-, and –CH2(CH3)2C-. In some embodiments, R 1The groups include -CH2-CH2-CH2-CH2-, and at least one of -CH2-CH2-, -CH2-CH2-CH2-, –CH(CH3)CH2-, or –CH2CH(CH3)-. In some embodiments, all R 1 The group is -CH2-CH2-CH2-CH2-. When all R 1 When the group is -CH2-CH2-CH2-CH2-, the L-divalent segment can be written as
[0026] L.
[0027] In the binary chain segment L, including any of the embodiments described above for L, each n independently represents a positive integer; for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 50, 100 or greater. In some embodiments, n may be at most 500 or greater.
[0028] Compounds that can be used as, for example, crosslinking agents comprise at least two X groups. Each X group is independently represented by the following formula: CH2=C(R)-C(O)-OVWC(O)-, Each R is independently hydrogen or methyl. In some embodiments, each R is hydrogen. In some embodiments, each R is methyl.
[0029] In the formula CH2=C(R)-C(O)-OVWC(O)-, each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group. In some embodiments, each V is independently an alkylene group optionally inserted with at least one ether bond. In some embodiments, each V is an alkylene group having 2 to 10, 2 to 8, 2 to 6, 2 to 4, 3 to 6, 3 to 8, or 3 to 10 carbon atoms.
[0030] In the formula CH2=C(R)-C(O)-OVWC(O)-, each W is independently O, S, or NR. 2 , where R 2 It is hydrogen or an alkyl group having up to 4 carbon atoms. In some embodiments, each W is independently O or NH. In some embodiments, each W is NH.
[0031] In some embodiments, the compound having at least two X groups and a divalent segment L has a number-average molecular weight of at least 1000 g / mol, 2000 g / mol, 3000 g / mol, 3500 g / mol, or 4000 g / mol and at most 54000 g / mol, 40000 g / mol, 30000 g / mol, or 20000 g / mol, as measured by gel permeation chromatography relative to a polystyrene standard at 40°C according to ASTM Test Method D3016-97 (2018). Specifically, polymers can be analyzed by gel permeation chromatography (GPC) using a Reliant GPC (Waters e2695 pump / autosampler) equipped with a Waters 2424 evaporative light scattering detector and PL-Gel-2 columns; each 300 × 7.5 mm; one 3 µm Mixed-E (nominal MW range up to 30,000 Daltons) and one 5 µm Mixed-D (nominal MW range 200 Daltons to 400,000 Daltons).
[0032] Compounds having at least two X groups and a divalent unit L can be prepared by nucleophilic addition of a primary amine group on a polyamine precursor compound to a reactant compound having carbonate, thiocarbonate, carbamate, or isocyanate groups and acrylate or methacrylate groups. An example of a usable compound of this type is ethyl 2-isocyanate methacrylate (“IEM”). Suitable polyamine precursors have a divalent segment L represented by the following formula:
[0033] L
[0034] As described above in any of its embodiments. Each divalent segment L is directly bonded to two N atoms, and each N atom is independently directly bonded to p additional divalent segments L and (2-p) H atoms, where p is 0, 1, or 2. In some embodiments, the polyamine precursor comprises less than 7 wt%, less than 6 wt%, less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt% of a secondary or tertiary amine group. Suitable polyamine precursors may be obtained under the trade name “DYNAMAR HC-1101” from 3M Company, St. Paul, Minnesota, or prepared, for example, as described in U.S. Patent 3,436,359 (Hubin et al.).
[0035] The compositions disclosed herein comprise 20% to 35% by weight of a compound having at least two X groups and a divalent L segment. In some embodiments, a crosslinking agent is present in an amount ranging from 25% to 35% by weight, based on the total weight of the acrylic functional compounds in the composition.
[0036] The compositions disclosed herein comprise at least 1% by weight of an acrylic monomer containing a carboxylic acid group, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the acrylic monomer containing a carboxylic acid group is present in an amount of at least 5%, 6%, or 10% by weight, based on the total weight of the acrylic functional compounds in the composition. The acrylic monomer containing a carboxylic acid group is present in an amount of less than 20% by weight, and in some embodiments, at most 19%, 18%, 17%, 16%, or 15% by weight, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the acrylic monomer containing a carboxylic acid group is present in an amount ranging from 1% to 19% by weight, 5% to 19% by weight, 5% to 18% by weight, or 6% to 16% by weight, based on the total weight of the acrylic functional compounds in the composition. Examples of suitable acrylic monomers containing a carboxylic acid group include methacrylic acid, acrylic acid, methacrylic acid, β-acryloyloxyethyl hydrosuccinate, and β-methacryloyloxyethyl hydrosuccinate. Many acrylic monomers containing carboxylic acid groups are commercially available, such as methacrylic acid (VISIOMER GMAA) from Evonik Performance Materials GmbH and β-methacryloyloxyethyl hydrosuccinate (NK ESTER SA) from Shin-Nakamura Co. Ltd., Arimoto, Japan. In some embodiments, the acrylic monomer containing the carboxylic acid group is methacrylic acid.
[0037] The compositions disclosed herein comprise acrylic monomers containing hydroxyl groups. Acrylic monomers containing hydroxyl groups can be used, for example, to provide compositions with improved adhesion to various plastics (in some embodiments, polyamides, acrylonitrile butadiene styrene (ABS), polycarbonate (PC), PC / ABS blends, polyvinyl chloride (PVC), and poly(meth)methacrylate (PMMA)). In some embodiments, the acrylic monomers containing hydroxyl groups are present in an amount of at least 5% by weight or 10% by weight and at most 25% by weight, 24% by weight, 23% by weight, 22% by weight, 21% by weight, or 20% by weight, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the acrylic monomers containing hydroxyl groups are present in an amount of at least 5% by weight and at most 25% by weight, at least 10% by weight and at most 24% by weight, or at least 10% by weight and at most 22% by weight, based on the total weight of the acrylic functional compounds in the composition. The level of acrylic monomers containing hydroxyl groups, selected in the range of 5% by weight and up to 25% by weight, can be used, for example, to provide compositions that have improved adhesion to a variety of plastics while maintaining relatively high water and moisture resistance.
[0038] Examples of suitable acrylic monomers containing hydroxyl groups include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2- and 3-hydroxypropyl acrylate, 2- and 3-hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, caprolactone mono(meth)acrylate (available under the trade name "SR-495B" from Sartomer) and other poly(e-caprolactone) mono[2-(meth)acryloyloxyethyl] esters, poly(e-caprolactone) mono[2-acryloyloxyethyl] esters, 2-hydroxy-3-alkoxy methacrylates, 2-hydroxy-3-alkoxy acrylates, and polyethylene glycol monoacrylates and methacrylates. Many acrylic monomers containing hydroxyl groups are commercially available, such as 2-hydroxyethyl methacrylate (available as VISIOMER HEMA 97 and HEMA 98 from Evonik Performance Materials, Inc.), hydroxypropyl methacrylate (available as VISIOMER HPMA 97 and HPMA 98 from Evonik Performance Materials, Inc.), ultra-high purity 2-hydroxyethyl methacrylate (available as VISIOMER UHP HEMA from Evonik Performance Materials, Inc.), polypropylene glycol monomethacrylate (available as MIRAMER M1051 from Miwon NorthAmerica, Exton, Pennsylvania), and CH2=CHC(O)O(CH2CH2O). 7-9H (for example, the product name "BLEMMER" may be purchased from Nippon Oil & Fats Company, Tokyo, Japan).
[0039] In some embodiments, the compositions disclosed herein further comprise at least one of alkyl acrylates or alkyl methacrylates. The alkyl groups of the alkyl acrylates or alkyl methacrylates may be straight-chain, branched, or cyclic (including polycyclic) and have 1 to 14, 1 to 12, or 1 to 10 carbon atoms. Including alkyl acrylates or alkyl methacrylates in the composition can, for example, provide relatively high water and moisture resistance while maintaining good adhesion to a variety of substrates. In some embodiments, the composition comprises methyl methacrylate. Methyl methacrylate is commercially available, including from Evonik Performance Materials Inc. as VISIOMER MMA. In some embodiments, the amount of at least one of alkyl acrylates, alkyl methacrylates, or methyl methacrylates in the composition is at least 20% by weight, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the amount of at least one of alkyl acrylates, alkyl methacrylates, or methyl methacrylates in the composition is at least 25% by weight or at least 30% by weight, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, based on the total weight of the acrylic functional compounds in the composition, the amount of at least one of alkyl acrylate, alkyl methacrylate, or methyl methacrylate in the composition is at most 50% by weight, 45% by weight, or 40% by weight. In some embodiments, based on the total weight of the acrylic functional compounds in the composition, the amount of at least one of alkyl acrylate, alkyl methacrylate, or methyl methacrylate in the composition is at least 20% by weight and at most 50% by weight, at least 25% by weight and at most 45% by weight, or at least 25% by weight and at most 40% by weight.
[0040] Lauryl methacrylate and isobornyl methacrylate can be used in some embodiments of the compositions disclosed herein. Such monomers are available from a variety of commercial sources, such as isobornyl methacrylate purchased as SR506 from Sartoma or as VISIOMER IBOA from Evonik Performance Materials, Inc., as SR423A from Sartoma or as VISIOMER IBOMA from Evonik Performance Materials, Inc., and lauryl methacrylate purchased as LMA 1214F from BASF, Florham Park, New Jersey. However, in some embodiments, the composition is free of lauryl methacrylate and / or isobornyl methacrylate, or contains up to 1% lauryl methacrylate and / or isobornyl methacrylate based on the total weight of the acrylic functional compounds in the composition. See, for example, Table 8 below, which shows that adhesives made from compositions of this disclosure that do not contain lauryl methacrylate or isoborneol methacrylate have better adhesion to a variety of plastics than adhesives that include lauryl methacrylate and isoborneol methacrylate.
[0041] In some embodiments, the compositions of this disclosure further comprise acrylic monomers containing phosphate or phosphonate groups. Such monomers can be used, for example, to enhance adhesion to metal substrates. Available acrylic monomers containing phosphate or phosphonate groups include ethylene glycol methacrylate phosphate and phosphonate-functionalized (meth)acrylate monomers (e.g., SIPOMERPAM resins from Solvay Specialty Polymers USA, LLC, or those from Amgen North America, Exton, Pennsylvania, such as MIRAMER SC1400 and MIRAMER SC1400A). Vinylphosphonic acid may also be useful. In some embodiments, the compositions of this disclosure further comprise acrylic monomers containing phosphonate groups. Based on the total weight of the acrylic functionalized compounds in the composition, the phosphonate or phosphate-functionalized acrylic monomers may be present in the composition in, for example, up to 10 wt%, 8 wt%, 6 wt%, 5 wt%, or 4 wt%. When present, the phosphonate or phosphate-functionalized acrylic monomers are present in an amount of at least 0.5% by weight, 1% by weight, or 2% by weight, based on the total weight of the acrylic functional compounds in the composition.
[0042] The compositions disclosed herein may also include other monofunctional free radical polymerizable monomers. Examples of usable monomers include 2-phenoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, alkoxylated lauryl (meth)acrylate, alkoxylated phenolic (meth)acrylate, alkoxylated tetrahydrofurfuryl (meth)acrylate, caprolactone (meth)acrylate, cyclotrimethylolpropane methyl acetal (meth)acrylate, ethylene glycol methyl ether (meth)acrylate, ethoxylated nonylphenol (meth)acrylate, isodecanyl (meth)acrylate, isooctyl (meth)acrylate, octadecyl (meth)acrylate (stearyl (meth)acrylate), tetrahydrofurfuryl (meth)acrylate, tridecyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and (methyl) Allyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, n-dodecyl acrylate, 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-ethoxypropyl acrylate or 3-ethoxypropyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, glycidyl acrylate, N-(2-(2-oxo-1-imidazolyl)ethyl)methacrylamide and methacryloylaminoethylvinyl urea (“MAEEU”) purchased from Solvay Specialty Polymers, USA, Inc. as SIPOMER WAM II, and combinations thereof.
[0043] Specific examples of other mono(meth)acrylate monomers that can be used in some embodiments of the compositions disclosed herein include 2-phenoxyethyl methacrylate (purchased as SR340 from Sartoma), cyclohexyl methacrylate (purchased as VISIOMER c-HMA from Evonik Performance, Inc.), benzyl methacrylate (purchased as MIRAMER M1183 from Amgen North America, Exton, PA), phenyl methacrylate (purchased as MIRAMER M1041 from Amgen North America), allyl methacrylate (purchased as VISIOMER AMA from Evonik Performance, Inc.), n-butyl methacrylate (purchased as VISIOMER n-BMA from Evonik Performance, Inc.), isobutyl methacrylate (purchased as VISIOMER i-BMA from Evonik Performance, Inc.), glyceryl methyl acetal methacrylate (purchased as VISIOMER RGLYFOMA from Evonik Performance, Inc.), and 2-(2-butoxyethoxy)ethyl methacrylate (purchased as VISIOMER c-HMA from Evonik Performance, Inc.). BDGMA was purchased from Evonik Performance Materials, Inc.; ethyl 2-isocyanate methacrylate (purchased from Showa Denko KK, Tokyo, Japan under the product number KarenzMOI); and mono-2-(methacryloyloxy)ethyl phthalate (HEMA phthalate) under the product number X-821-2000 was purchased from ESSTECH, Inc., Essington, Pennsylvania.Essington, Pennsylvania), 2-(methacryloyloxy)ethyl maleate (HEMA maleate, purchased from Yishi Technology Co., Ltd. under product number X-846-0000), methoxydiethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. under product number M-20G), methoxytriethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. under product number M-30G), methoxytetraethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. under product number M-40G), The following products were purchased from Shin-Nakamura Chemical Industry Co., Ltd.: methoxytripropylene glycol methacrylate (purchased as M-30PG from Shin-Nakamura Chemical Industry Co., Ltd.), butoxydiethylene glycol methacrylate (purchased as B-20G from Shin-Nakamura Chemical Industry Co., Ltd.), phenoxyethylene glycol methacrylate (purchased as PHE-1G from Shin-Nakamura Chemical Industry Co., Ltd.), phenoxydiethylene glycol methacrylate (purchased as PHE-2G from Shin-Nakamura Chemical Industry Co., Ltd.), and dicyclopentadienoxyethyl methacrylate (purchased as FANCRYL...). FA-512M was purchased from Hitachi Chemical, Tokyo, Japan; dicyclopentyl methacrylate (FANCRYL FA-513M was purchased from Hitachi Chemical, Japan); isobornylcyclohexyl methacrylate (designer Molecules, Inc., San Diego, California, product number MM-304 was purchased from Designer Molecules, Inc., San Diego, California); 4-methacryloyloxyethyl trimellitic anhydride (designer Molecules, Inc., product number A-304 was purchased from Designer Molecules, Inc.); 2-methacryloyloxyethyl phenylcarbamate (polysciences, Inc., Warrington, Pennsylvania, Pennsylvania, product number MM-304 was purchased from Poly ... Inc., Pennsylvania, Pennsylvania, Pennsylvania, product number MM-304 was purchased from Polysciences, Inc., Warrington, Inc., Pennsylvania, Pennsylvania, Pennsylvania, Pennsylvania, Pennsylvania, Pennsylvania, Pennsylvania, Pennsylvania, Pennsylvania, MADAME (purchased from Evonik Performance Materials, Inc.), 3-dimethylaminopropylmethacrylamide (purchased from Evonik Performance Materials, Inc. under the name VISIOMER DMAPMA), and combinations thereof.
[0044] The compositions disclosed herein also comprise at least one free radical initiator (i.e., an initiator for free radical polymerization). The free radical initiator can be a single compound or a combination of compounds, referred to as a free radical initiator system.
[0045] In some implementations, the radical initiator is a redox initiator system because single-electron transfer redox reactions can be an efficient method for generating free radicals under mild conditions. Redox initiator systems have been described, for example, in advance in polymer science (…). Progress in Polymer Science (1999), Volume 24, pp. 1149-1204.
[0046] In some embodiments, the redox initiator system is a blend of a peroxide and an amine, wherein polymerization is initiated by the decomposition of the organic peroxide, which is activated by a redox reaction with an amine reducing agent. Typically, the peroxide is benzoyl peroxide, and the amine is a tertiary amine. Aromatic tertiary amines are suitable for generating primary groups, among which N,N-dimethyl-4-toluidine (“DMT”) is the most common amine reducing agent.
[0047] In some embodiments, the redox curing initiator system comprises a barbituric acid derivative and a metal salt. In some embodiments, the barbituric acid / metal salt curing initiator system may also comprise an organic peroxide, an ammonium chloride salt (e.g., benzyltributylammonium chloride), or a mixture thereof.
[0048] Examples of free radical initiators based on barbituric acid include redox initiator systems having (i) a barbituric acid derivative and / or malonyl sulfonamide and (ii) an organic peroxide selected from monofunctional or polyfunctional carboxylic acid peroxide esters. Examples of available barbituric acid derivatives include 1,3,5-trimethylbarbituric acid, 1,3,5-triethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,5-dimethylbarbituric acid, 1-methyl-5-ethylbarbituric acid, 1-methyl-5-propylbarbituric acid, 5-ethylbarbituric acid, 5-propylbarbituric acid, 5-butylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, and thiobarbituric acid, as mentioned in the published German patent application DE 42 19 700 A1 (Imai et al.).
[0049] Barbiturates and barbiturates described in U.S. Patents 3,347,954 (Bredereck et al.) and 9,957,408 (Thompson), as well as malonyl sulfonamides disclosed in European Patent No. EP 0 059 451 B1 (Schmitt et al.), may also be used in embodiments of this disclosure. Examples of malonyl sulfonamides include 2,6-dimethyl-4-isobutylmalonyl sulfonamide, 2,6-diisobutyl-4-propylmalonyl sulfonamide, 2,6-dibutyl-4-propylmalonyl sulfonamide, 2,6-dimethyl-4-ethylmalonyl sulfonamide, or 2,6-dioctyl-4-isobutylmalonyl sulfonamide.
[0050] Barbiturate-based radical initiators typically comprise monofunctional or polyfunctional carboxylic acid peroxides as organic peroxides. Within the meaning of this disclosure, carbonate peroxides are also included in the category of polyfunctional carboxylic acid peroxides. Suitable examples include diisopropyl carbonate-peroxide diester, neodecanoic acid-tert-butyl-peroxide, neodecanoic acid-tert-amyl-peroxide, maleic acid-tert-butyl-monoperoxide, benzoic acid-tert-butyl-peroxide, 2-ethylhexanoic acid-tert-butyl-peroxide, 2-ethylhexanoic acid-tert-amyl-peroxide, monoisopropyl carbonate-monotert-butyl-peroxide, dicyclohexyl carbonate-peroxide, dimyristyl carbonate-peroxide, and carbonate... Diceryl peroxide, di(2-ethylhexyl)-peroxide, tert-butyl-peroxy-(2-ethylhexyl)-peroxide or 3,5,5-trimethylhexanoic acid-tert-butyl-peroxide, benzoic acid-tert-pentyl-peroxide, acetic acid-tert-butyl-peroxide, di(4-tert-butyl-cyclohexyl)-peroxide, neodecanoic acid-isopropylbenzene-peroxide, neopentanoic acid-tert-pentyl-peroxide and neopentanoic acid-tert-butyl-peroxide.
[0051] Specifically, in some embodiments of this disclosure, tert-butyl-peroxy-(2-ethylhexyl) carbonate (available from Arkema, Inc., King of Prussia, PA, via LUPEROX TBEC) or tert-butyl-peroxide 3,5,5-trimethyl-hexanoate (available from Arkema, via LUPEROX 270) can be used as organic peroxides.
[0052] Metal salts that can be used with barbituric acid derivatives may include transition metal complexes, particularly salts of cobalt, manganese, copper, and iron. When the metal salt is a copper compound, it may have the general formula CuXn, where X is an organic and / or inorganic anion, and n = 1 or 2. Examples of suitable copper salts include copper chloride, copper acetate, copper acetylacetonate, copper naphthenate, copper salicylate, or complexes of copper with thiourea or ethylenediaminetetraacetic acid, and mixtures thereof. In some embodiments, the copper salt is copper naphthenate.
[0053] Another redox initiator system applicable to embodiments of this disclosure comprises an inorganic peroxide, an amine-based reducing agent, and a promoter, wherein the amine may be an aromatic and / or aliphatic amine, and the polymerization promoter is at least one selected from the group consisting of sodium benzenesulfinate, sodium p-toluenesulfinate, sodium 2,4,6-triisopropylbenzenesulfinate, sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sodium bisulfate, and potassium bisulfate. Examples of inorganic peroxides that can be used in this system are persulfates, as described in U.S. Patent 8,545,225 (Takei et al.).
[0054] In some embodiments, the compositions of this disclosure comprise a free radical initiator comprising a metal salt (e.g., copper naphthenate) and an ammonium salt (e.g., benzyltributylammonium chloride). In some embodiments, the compositions comprise a curing initiator system comprising a barbituric acid derivative and a metal salt, and optionally comprising at least one of an organic peroxide and an ammonium chloride salt.
[0055] The composition may include at least one photoinitiator, alone or in combination with other free radical initiators, which is activated by light (typically ultraviolet (UV) lamps), but other light sources such as LED lamps, xenon flash lamps and lasers may also be used if the photoinitiator is appropriately selected.
[0056] Available photoinitiators include those known to be usable for photocuring free radical polyfunctional (meth)acrylates. Examples of suitable photoinitiators include benzoin and its derivatives such as α-methylbenzoin; α-phenylbenzoin; α-allylbenzoin; α-benzylbenzoin; benzoin ethers such as benzoyl dimethyl ketal (e.g., available as OMNIRAD BDK from IGM Resins USA Inc., St. Charles, Illinois), benzoin methyl ether, benzoin ethyl ether, benzoin n-butyl ether; acetophenone and its derivatives such as 2-hydroxy-2-methyl-1-phenyl-1-propanone (e.g., available as OMNIRAD 1173 from IGM Resins USA Inc.) and 1-hydroxycyclohexylphenyl ketone (e.g., available as OMNIRAD 184 from IGM Resins USA Inc.); 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholino)-1-propanone (e.g., available as OMNIRAD BDK from IGM Resins USA Inc.). 907 was purchased from IGM Resins, USA; 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholino)phenyl]-1-butanone (e.g., purchased from IGM Resins, USA as OMNIRAD 369) and triarylphosphine and phosphine oxide derivatives, such as ethyl 2,4,6-trimethylbenzoylphenylphosphonate (e.g., purchased from IGM Resins, USA as TPO-L) and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (e.g., purchased from IGM Resins, USA as OMNIRAD 819).
[0057] Other examples of available photoinitiators include pivaloin ether, anethole ether, anthraquinones (e.g., anthraquinone, 2-ethylanthraquinone, 1-chloroanthraquinone, 1,4-dimethylanthraquinone, 1-methoxyanthraquinone, or benzoanthraquinone), halomethyltriazines, benzophenone and its derivatives, iodonium and sulfonium salts, titanium complexes such as bis(n5-2,4-cyclopentadien-1-yl)-bis[2,6-difluoro-3-(1H-pyrrolo-1-yl)phenyl]titanium (e.g., available under the trade name CGI 784DC from BASF, Florem Park, NJ); halomethyl-nitrobenzene (e.g., 4-bromomethylnitrobenzene), and combinations of photoinitiators in which one component is a monoacylphosphine oxide or a diacylphosphine oxide (e.g., available under the trade names IRGACURE 1700, IRGACURE 1800, and IRGACURE). Purchased in 1850 from BASF, Florem Park, New Jersey, and in OMNIRAD 4265 from IGM Resins USA.
[0058] Free radical initiators can also be thermally activated free radical initiators, such as azo initiators (e.g., azobisisobutyronitrile) or peroxides (e.g., benzoyl peroxide).
[0059] The free radical initiator can be used in the composition in an amount sufficient to allow the curable composition to have a adequate rate of curing free radical reaction when polymerization is initiated; these amounts can be readily determined by those skilled in the art. In some embodiments of this disclosure, the free radical initiator is present in the curable composition at a level of 0.1% to 10% by weight, or 0.5% to 5% by weight, of the free radical polymerizable component in the composition; however, this is not required.
[0060] In some embodiments, the compositions disclosed herein comprise, based on the total weight of the acrylic functional compounds in the composition, 5% to 19% by weight of an acrylic monomer containing a carboxylic acid group, 5% to 25% by weight of an acrylic monomer containing a hydroxyl group, 20% to at most 50% by weight of methyl methacrylate, 0.5% to 10% by weight of an acrylic monomer containing a phosphonate group, and 20% to 35% by weight of a compound containing a divalent segment L and at least two X groups, and based on the weight of the curable composition, 0.1% to 10% by weight of at least one free radical initiator. In some embodiments, the compositions of this disclosure consist of, or substantially consist of, 20% to 35% by weight of an acrylic monomer comprising a carboxylic acid group, 5% to 24% by weight of an acrylic monomer comprising a hydroxyl group, 20% and at most 50% by weight of methyl methacrylate, 0.5% to 10% by weight of an acrylic monomer comprising a phosphonate group, and 20% to 35% by weight of a compound comprising a divalent segment L and at least two X groups. In this context, “substantially consists of” means that the composition does not contain other radical-reactive monomers. In some embodiments of these embodiments, the composition comprises 0.1% to 10% by weight of at least one radical initiator based on the total weight of the curable composition.
[0061] The compositions disclosed herein may include other components that can be used in, for example, sealant and adhesive compositions. For example, the compositions may contain at least one of the following: toughening agents (e.g., acrylic core / shell polymers; styrene-butadiene / methacrylate core / shell polymers; acrylonitrile-butadiene rubber), plasticizers (e.g., aliphatic and aromatic hydrocarbons, alkyl esters, alkyl ethers, aryl esters and aryl ethers), tackifiers, corrosion inhibitors, UV stabilizers, antioxidants, free radical inhibitors, flame retardants, thixotropic agents such as pyrolytic silica, dyes, pigments (e.g., iron oxide, brick dust, carbon black and titanium dioxide), reinforcing agents (e.g., silica, magnesium sulfate, calcium sulfate and beryllium aluminum silicate), clays such as bentonite, other suitable fillers (e.g., glass beads, talc and calcium metasilicate), dispersants, wetting agents, adhesion promoters (e.g., silane coupling agents), antistatic agents, thermally and / or electrically conductive particles, foaming agents and hollow polymers or ceramic microspheres (e.g., glass bulbs). In some embodiments, the compositions disclosed herein contain fillers. Further examples of fillers that can be used in some embodiments of the compositions disclosed herein include at least one of the following: microfibrillated polyethylene, pyrolytic silica, talc, wollastonite, aluminosilicate clay (e.g., hydrous kaolin), phlogopite, calcium carbonate, kaolin, metal oxides (e.g., barium oxide, calcium oxide, magnesium oxide, zirconium oxide, titanium oxide, zinc oxide), and nanoparticle fillers (e.g., nano silica, nano zirconium oxide).
[0062] The compositions disclosed herein may be provided as a single-component or two-component composition, depending, for example, on the chosen radical initiator. When using a radical initiator system comprising a combination of components, some of the components may be included in a first portion of the two-component composition, while others may be included in a second portion of the two-component composition. In some embodiments, if the composition disclosed herein is the first portion of a two-component composition, the first portion may include at least one of a metal salt or ammonium chloride salt as described above in any of their embodiments, and the second portion may include at least one of a barbituric acid derivative and an organic peroxide. The second portion may be, for example, in the form of a paste, comprising at least one of a plasticizer or other diluent and optionally a toughening agent, dye, pigment, tackifier, or filler, as described above. For example, some peroxide pastes are commercially available. An example of a usable second portion is an acrylic adhesive accelerator from 3M Company, St. Paul, Minnesota, under the trade name “3MSCOTCH-WELD DP8410NS”.
[0063] In some embodiments, if the composition of this disclosure is the first part of a two-part composition, the first and second parts can be combined in any suitable volume ratio. For example, the first and second parts can be combined in a volume ratio ranging from about 5:100 to about 100:1, from about 10:100 to about 50:1, or from about 1:1 to 20:1.
[0064] The first and second portions can be located in any suitable system or kit for containing, mixing, and dispensing the first and second portions. This system can be suitable for large-scale industrial applications or small-scale applications. Any system may include a first chamber and a second chamber for storing the respective first and second portions. The dimensions of the chambers may be set to suit any application and formed of plastic, metal, or any other suitable material. A dispenser may be adapted to receive the first and second portions and dispense the mixture of the first and second portions onto a substrate. The dispenser may be used to facilitate mixing of the first and second portions, or a mixing chamber may be located upstream of the dispenser and in fluid communication with the first and second chambers. The mixing chamber may be adapted to rotate to facilitate mixing, or the mixing chamber may include multiple baffles to induce rotation of the first and second portions.
[0065] To facilitate movement of the first and second portions, the system may include elements such as one or more plungers or one or more pumps. One or more plungers may be used in a handheld system. In these embodiments, a user may push one or both plungers between at least a first position and a second position to force the first and second portions through the system. If one plunger is present, the first and second portions can be dispensed in equal volumes or a predetermined volume ratio.
[0066] Pumps can be used in industrial applications where a large or continuous supply of a first and a second portion is dispensed. These systems may include one or more pumps in fluid communication with the first and second chambers. The one or more pumps may be located downstream of the first and second chambers, but upstream of the mixing chamber. In embodiments of a system in which two pumps are in fluid communication with the respective first and second chambers, the pumps may be adapted or controlled to pump equal volumes of the first and second portions, or to pump different amounts of the portions according to a predetermined volume ratio.
[0067] The compositions disclosed herein can be at least partially cured by exposure to photochemical electromagnetic radiation (e.g., ultraviolet and / or visible light), thermal energy (e.g., in an oven, infrared radiation, or thermal conduction), by exposure to oxygen, by combining two portions of a two-part composition, or any combination thereof.
[0068] After at least partial curing, a crosslinked composition is typically obtained, and if fully cured, it can be suitable as a structural adhesive for bonding two adherends. In such applications, the composition is typically sandwiched between the adherends and cured at least partially; for example, sufficient to achieve at least the desired level of bond strength.
[0069] The compositions disclosed herein can be used, for example, to bond a first substrate to a second substrate to provide an bonded article. Many types of substrates can be bonded to the compositions disclosed herein, such as metals (e.g., stainless steel or aluminum), glass (e.g., which may be coated with indium tin oxide), polymers (e.g., plastics, rubber, thermoplastic elastomers, or thermosetting materials), or composite materials. Composite materials can be made from any two or more constituent materials with different physical or chemical properties. When components are combined to prepare composite materials, materials with properties different from those of the individual components are typically obtained. Some examples of useful composite materials include fiber-reinforced polymers (e.g., carbon fiber-reinforced epoxy resins and glass-reinforced plastics); metal matrix compositions; and ceramic matrix composites. Available polymer substrates for bonding include polymers such as polyolefins (polypropylene, polyethylene, high-density polyethylene, polypropylene blends), polyamide 6 (PA6), polyamide 6,6, acrylonitrile butadiene styrene (ABS), polycarbonate (PC), PC / ABS blends, polyvinyl chloride (PVC), polyamide (PA), polyurethane (PUR), thermoplastic elastomers (TPE), polyoxymethylene (POM), polystyrene, poly(meth)methyl acrylate (PMMA), polyvinyl chloride (PVC), polyetheretherketone (PEEK), and combinations thereof. The substrate may also include a metallic coating on such polymers. The compositions disclosed herein can be used, for example, to bond electronic products as well as automotive and aerospace components.
[0070] In some embodiments, a first substrate can be bonded to a second substrate by: combining the composition with an accelerator to provide an adhesive composition; applying the composition of this disclosure to at least a portion of a surface of the first substrate; adhering the first and second substrates using the adhesive composition; and allowing the adhesive composition to cure to prepare an bonded article. While listing specific curing temperatures applicable to all cases is impractical, generally suitable temperatures are in the range of about 23°C to about 200°C. In some embodiments, advantageously, the composition can be cured at room temperature (e.g., 23°C to 30°C) for, for example, at least 60 minutes, 90 minutes, 120 minutes, 6 hours, 12 hours, 24 hours, 48 hours, or 72 hours.
[0071] As shown in the following examples, the compositions of this disclosure can be cured at room temperature to provide an adhesive with a glass transition temperature of 111°C to 114°C. The adhesive has an elongation of 59% to 63%, which makes it suitable for bonding substrates at low temperatures, as shown in Table 7. The adhesive can bond a variety of materials, including metals and many plastic substrates, including polyamide (nylon), ABS, PVC, and PMMA, as shown in Table 8. As shown in Tables 10 and 11, the adhesive bonding is resistant to water or high humidity.
[0072] Some implementation schemes disclosed herein
[0073] In a first embodiment, this disclosure provides a composition comprising: Based on the total weight of acrylic functional compounds in the composition, at least 1% by weight and less than 20% by weight of acrylic monomers containing carboxylic acid groups; At least one of alkyl acrylates or alkyl methacrylates; Acrylic monomers containing hydroxyl groups; and Based on the total weight of the acrylic functional compound in the composition, 20% to 35% by weight of a compound comprising a divalent segment L and at least two X groups, wherein the divalent segment L is represented by the following formula:
[0074] L
[0075] Each of the two-valent segments L is directly bonded to: i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group. ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or iii) A secondary N atom, which is directly bonded to another divalent chain segment L or X group; and a tertiary N atom, which is directly bonded to p other divalent chain segments L and (2-p) X groups, where p is 0, 1 or 2. Each R 1 Independently represents an alkylene group having 1 to 4 carbon atoms, provided that R 1 At least some of the groups are -CH2-CH2-CH2-CH2-, where each n independently represents a positive integer, and where each X group is independently represented by the following formula: CH2=C(R)-C(O)-OVWC(O)- Each W is independently O, S, or NR. 2 , where R 2It is hydrogen or an alkyl group having up to 4 carbon atoms, and wherein each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group.
[0076] In a second embodiment, this disclosure provides a composition according to the first embodiment, wherein at least 50% of R 1 The group is -CH2-CH2-CH2-CH2-.
[0077] In a third embodiment, this disclosure provides a composition according to the first or second embodiment, wherein the divalent L-segment is represented by the following formula: , Each n represents a positive integer.
[0078] In a fourth embodiment, this disclosure provides a composition according to any one of the first to third embodiments, wherein an acrylic monomer containing a hydroxyl group is present in an amount of at least 5% by weight or 10% by weight and at most 25% by weight, 24% by weight, 23% by weight, 22% by weight, 21% by weight or 20% by weight, based on the total weight of the acrylic functional compound in the composition.
[0079] In a fifth embodiment, this disclosure provides a composition according to any one of the first to fourth embodiments, wherein at least one of the alkyl acrylates or alkyl methacrylates is methyl methacrylate.
[0080] In a sixth embodiment, this disclosure provides a composition according to any one of the first to fifth embodiments, the composition comprising at least 20% and at most 50% by weight of methyl methacrylate based on the total weight of the acrylic functional compounds in the composition.
[0081] In a seventh embodiment, this disclosure provides a composition according to any one of the first to sixth embodiments, wherein an acrylic monomer comprising a carboxylic acid group is present in an amount of at least 5% by weight and at most 19%, 18%, 17%, 16%, or 15% by weight, based on the total weight of the acrylic functional compound in the composition.
[0082] In the eighth embodiment, this disclosure provides a composition according to any one of the first to seventh embodiments, wherein the composition is free of lauryl methacrylate or contains up to 1% lauryl methacrylate based on the total weight of the acrylic functional compounds in the composition.
[0083] In a ninth embodiment, this disclosure provides a composition according to any one of the first to eighth embodiments, wherein the composition is free of isoborneol methacrylate or contains up to 1% isoborneol methacrylate based on the total weight of the acrylic functional compounds in the composition.
[0084] In a tenth embodiment, this disclosure provides a composition according to any one of the first to ninth embodiments, the composition comprising essentially the following: 20% to 35% by weight of an acrylic monomer containing a carboxylic acid group, 5% to 24% by weight of an acrylic monomer containing a hydroxyl group, 20% and at most 50% by weight of methyl methacrylate, 0.5% to 10% by weight of an acrylic monomer containing a phosphonate group, and 20% to 35% by weight of a compound containing a divalent segment L and at least two X groups, based on the total weight of the acrylic functional compounds in the composition.
[0085] In the eleventh embodiment, this disclosure provides a composition according to any one of the first to tenth embodiments, the composition further comprising a toughening agent.
[0086] In the twelfth embodiment, this disclosure provides a composition according to any one of the first to eleventh embodiments, the composition further comprising a filler.
[0087] In the thirteenth embodiment, this disclosure provides a composition according to any one of the first to twelfth embodiments, the composition further comprising a free radical initiator.
[0088] In the fourteenth embodiment, this disclosure provides a composition according to any one of the first to thirteenth embodiments, the composition further comprising a free radical initiator.
[0089] In the fifteenth embodiment, this disclosure provides a composition according to any one of the first to fourteenth embodiments, the composition also being packaged as a first part of a two-part adhesive composition, wherein the second part comprises a free radical initiator.
[0090] In a sixteenth embodiment, this disclosure provides an adhesive comprising a composition according to any one of the first to fourteenth embodiments, the composition being at least partially cured with a free radical initiator, wherein the adhesive composition has a glass transition temperature in the range of 90°C to 130°C.
[0091] In a seventeenth embodiment, the present disclosure provides an adhesive comprising a composition according to any one of the first to fourteenth embodiments, the composition being at least partially cured with a free radical initiator, wherein the composition has an elongation in the range of 30% to 80%.
[0092] In the eighteenth embodiment, this disclosure provides an article of manufacture that is bonded using a composition according to any one of the first to fourteenth embodiments, the composition being at least partially cured with a free radical initiator, wherein the article comprises at least one of polyamide, acrylonitrile butadiene styrene, poly(meth)methacrylate, or polyvinyl chloride.
[0093] In a nineteenth embodiment, this disclosure provides a method for preparing an adhesive article comprising a first substrate and a second substrate, the method comprising: The composition according to any one of the first to fourteenth embodiments is combined with a free radical initiator to provide an adhesive composition; The adhesive composition is applied to at least one of the first substrate or the second substrate; Adhesive composition is used to adhere the first substrate and the second substrate; and Allow the adhesive composition to cure at least partially in order to prepare an adhesive article.
[0094] In a twentieth embodiment, this disclosure provides a method according to a nineteenth embodiment, wherein at least one of the first substrate or the second substrate comprises at least one of polyamide, acrylonitrile butadiene styrene, poly(meth)methacrylate, or polyvinyl chloride.
[0095] The purposes and advantages of this disclosure are further illustrated by the following non-limiting embodiments, but the specific materials and quantities referenced in these embodiments, as well as other conditions and details, should not be construed as undue limitation of this disclosure.
[0096] Example
[0097] Unless otherwise specified, all parts, percentages, proportions, etc., used in the examples and other parts of the specification are by weight, and all reagents used in the examples are derived from or available from general chemical suppliers, such as Sigma-Aldrich, St. Louis, MO, USA, or can be synthesized by conventional methods. The following abbreviations are used in this section: in = inch, g = gram, min = minute, ℃ = degree Celsius, ℉ = degree Fahrenheit, RH = relative humidity, Hz = hertz, J = joule, ° = degree angle, μm = micrometer, and rpm = revolutions per minute.
[0098]
[0099] Test methods
[0100] Tensile test of cured film
[0101] A cured film of the composition was prepared by extruding the two-part composition of Example 1 or Exemplary Example A or B onto a silicone polyester liner using a static mixer. Using a second silicone polyester liner, an adhesive film was prepared between the two liners to a thickness of approximately 1 mm (0.04 in) using a simple doctor blade coater. The adhesive film was allowed to cure at room temperature for at least 24 hours prior to testing. Tensile elongation was measured according to ASTM Standard D638–14, 2015, “Standard Test Method for Tensile Properties of Plastics,” using a TYPE-V die for sample cutting and a clamp test speed of 50.8 mm (2 in) / min.
[0102] Dynamic mechanical analysis (DMA)
[0103] Membrane samples were prepared using the membrane prepared for tensile testing as described above. The membrane samples were cut into approximately 5-6 mm wide × 1 mm thick × 57 mm long pieces (0.20 in - 0.24 in × 0.04 in × 2.25 in) and tested using a double cantilever clamp on a DMAQ800 (TA Instruments Inc., New Castle, DE) with the following settings: frequency = 1 Hz, oscillation amplitude = 15 μm, and minimum oscillation force = 0.02 N. The membrane samples were equilibrated to -50 °C (122 °F) and held at this temperature for five minutes, then gradually increased to 200 °C (392 °F) at a rate of 3.0 °C (37.4 °F) / minute.
[0104] Overlap shear test
[0105] Overlap shear test specimens were prepared on various substrates using the resulting mixed adhesives. All Nylon 6,6, Nylon 6, 30% glass-filled Nylon 6,6, PEEK, PEI / Ultem, PBT, PPO, ABS, and PVC specimens obtained from Plastics International, Eden Prairie, MN, measured 6.35 × 25.4 × 101.6 mm (1 / 4 × 1 × 4 in). Kalix 9950 specimens obtained from Aeromat Plastics, Burnsville, MN, measured 2.54 × 10.16 × 0.311 cm (1 in × 4 in × 0.13 in); Aeromat Plastics prepared the specimens by extruding Kalix 9950 granules obtained from Solvay Co., Brussels, Belgium. The BASF “Ultramide” sample and the PMMA, polycarbonate and Green FR-4 samples, obtained from Plastics International, were 3.18 × 25.4 × 101.6 mm (1 / 8 × 1 × 4 in). All plastic samples were wiped with isopropyl alcohol only before bonding. The aluminum, cold-rolled steel and stainless steel samples, obtained from Joseph t. Ryerson and Son, Inc., Coon Rapids, MN, were 2.54 × 10.16 × 0.16 cm (1 in × 4 in × 1 / 16 in) and were prepared using one of two methods: (1) wiped with isopropyl alcohol only before bonding, or (2) ground with a pad of the trade name “SCOTCH BRITE” (3M Corporation, St. Paul, Minnesota) and mounted on an elastic palm sander, and then wiped with isopropyl alcohol before bonding. When preparing the overlap shear samples, a 1.27 cm (1 / 2 in) overlap was used. The adhesive layer was clamped with a long-tail clamp during curing and the clamp was removed after 24 hours at 25°C. Overlap shear tests were performed on metal samples using a 5,620 lb (25 kN) force sensor, and on plastic samples using a 2,250 lb (10 kN) force sensor. The plastic overlap shear samples were run at 50.8 mm (2 in) / min, and the metal overlap shear samples were run at 2.54 mm (0.1 in) / min. Peak stress values (psi) are reported, and each value is the average of three samples.
[0106] Heat / humidity cycling and thermal shock
[0107] ASTM D1002 samples were used in this test (pulling speed 2.54 mm (0.10 in) / min). The adhesive layer thickness was 0.254 mm (0.010 in) and was determined by the diameter of the glass spacer beads in the formulation. Samples were cured at room temperature (approximately 23°C) for 3 days before exposure to the conditions. Isopropyl alcohol was applied to all substrates before bonding. Three samples were tested, and the results for each test condition were averaged.
[0108] This test was conducted to compare the performance of Example 1 and Exemplary Examples A and B on an aluminum substrate and nylon 6,6. Aluminum and nylon 6,6 samples were subjected to thermal / humidity cycling tests at -40°C (104℉) and +85°C (185℉) / 80% RH. The overlap shear strength retention value was reported, where strength retention refers to the overlap shear value of the test sample relative to the control test sample exposed to the test environment. The % strength retention was reported. Table 2 shows the key parameters for the thermal / humidity cycling test and the thermal shock test, respectively.
[0109]
[0110] Water immersion overlapping shear test
[0111] Nine overlapping shear samples were prepared using sandblasted FR4 glass epoxy resin specimens (obtained from Plastics International, measured 2.54 × 10.16 × 0.318 cm (1 in × 4 in × 0.125 in)). The OLS samples were bonded with a 1.27 cm (0.5 in) overlap and the adhesive was allowed to cure for at least 24 hours. Three of the nine samples served as controls and were stored in the laboratory under ambient conditions. The remaining six OLS samples were placed in 1-gallon wide-mouth glass flasks, and the flasks were filled with water to completely submerge the samples. The flasks were placed in an oven set to 60°C (140°F). After one week, three samples were removed from the flasks and allowed to equilibrate to room temperature for approximately one hour. The OLS (peak stress) of the three exposed samples and the three control samples was then tested, and the % strength retention was reported. After two weeks, the OLS (peak stress) of the remaining three exposed samples was tested and compared with the controls. The % strength retention was reported. Note that in some cases, only six OLS samples were tested (three control samples and three two-week exposed samples). The results of the test are reported in Table 10.
[0112] Mud application test
[0113] Ten overlapping shear samples were prepared using abraded aluminum specimens, sourced from Joseph T. Ryerson and Son, Coon Lapis, Minnesota, measuring 2.54 × 10.16 × 0.16 cm (1 in × 4 in × 1 / 16 in). The specimens were ground using a mat labeled “SCOTCH BRITE” (3M, St. Paul, Minnesota) and mounted on an electric palm sander, subsequently wiped with MEK solvent before bonding. The OLS samples were bonded with a 1.27 cm (0.5 in) overlap and the adhesive was allowed to cure for at least 24 hours. Five of the ten samples served as controls and were stored in the laboratory under ambient conditions. The remaining five OLS samples were carefully wrapped in 100% cotton wadding. The packaged samples were placed in a bag bearing the trade name "ZIPLOC" (SC Johnson and Son, Inc., Racine, WI), and distilled water was added in an amount ten times the total weight of the cotton wadding used. This bag was sealed and placed in a second, identically sealed bag. The double-bag sample was then placed on an aluminum tray and placed in an oven set to 71°C (160°F) for two weeks. After two weeks in the 71°C (160°F) oven, the sample was immediately placed in a freezer at -17.8°C (0°F) for two hours. After two hours in the freezer, the sample was thawed for two hours and then immediately subjected to a standard overlapping shear test at 2.54 mm (0.1 in) / min using a 5620-lb force sensor. The OLS of both the mud-coating sample and the control sample were tested simultaneously, and the % strength retention was again reported based on the average of all controls. The results of this test are reported in Table 11.
[0114] Side impact test
[0115] Each sample formulation was individually loaded into 10 sections of a 10:1 dual-cylinder dispenser, with an accelerator from SCOTCH-WELD DP8810NS acrylic adhesive (3M, St. Paul, Minnesota) used in one section of the dispenser in each case. All adhesives were prepared by dispensing the sample formulation and accelerator into the adhesive composition used to prepare impact test specimens on a milled aluminum substrate via a static mixing head. The impact specimens were 2.54 cm × 10.16 cm × 0.16 cm (1 in × 4 in × 0.063 in) aluminum specimens with a 1.27 cm (0.5 in) overlap. The adhesive layer was clamped with a long-tail clamp during curing and the clamp was removed after 24 hours at 25°C (77℉). The specimens were tested on a CP9050 impact pendulum (Instron, Norwood, Mass.) where the specimens were held in the clamp and impacted against the edge of the adhesive area. The test parameters were ISO 179-1, using a 21.6J hammer dropped at a 150.0° angle.
[0116] Bell peel strength test
[0117] Follow the procedure outlined in ASTM D3167. Apply adhesive to an etched aluminum substrate (1.0" wide × 0.063" thick × 8.0" long), adding 17 mil spacer beads to the applied adhesive before bonding. Then apply a second aluminum substrate (1.0" wide × 0.020" thick × 10" long) to the adhesive and compress the bonded aluminum test specimen using a metal plate of approximately 10 lb. Allow the adhesive to cure for at least three days. After curing, perform a peel test using a 200 lb force sensor and a floating roller device. Pull the specimen at 6' / min.
[0118] Preparation of methacryloyloxyurea-terminated branched diamine poly(tetrahydrofuran) (EPX-IEM)
[0119] DYNAMAR HC-1101 (“HC-1101”) was heated at 65°C to melt the solid material and reduce its viscosity. Molten HC-1101 (245.0 g) was loaded into a three-necked round-bottom flask equipped with a distillation head, thermocouple, and top stirrer. The flask was purged with nitrogen and heated to 7°C. ℃. Methyl ethyl ketone (60 mL) was added to the highly viscous heated “HC-1101” with stirring. Then, the same amount of methyl ethyl ketone was distilled off under vacuum to obtain dry “HC-1101”. 5.32 g of IEM was added dropwise to the dry “HC-1101” under nitrogen atmosphere, and stirring was continued at 70℃ for 16 hours. Isocyanate consumption was monitored by transmission-FTIR spectroscopy. The resulting material was then subjected to 7... Discharged at ℃ to provide 196.2g (78% yield) of viscous, light yellow oil, which solidifies upon cooling to ambient temperature.
[0120] Example 1
[0121] Example 1 was prepared by combining the components shown in Table 3 in a polypropylene MAX 600 DAC cup (FlackTek, Inc., Landrum, SC, South Carolina). Each of the material components in each group was rapidly mixed as described. First, hydroxyethyl methacrylate (HEMA), methacrylic acid, benzyltributylammonium chloride (N+CL-), and methoxyethylhydroquinone (MEHQ) were combined and rapidly mixed at 1500 rpm for 4 minutes using a DAC 400.2 VAC (FlackTek). Then, the solid EPX-IEM material was melted in an oven at 71°C (160°F) for several hours, and the molten material was added to the rapid mixer cup, and the resulting material was rapidly mixed at 2250 rpm for 4 minutes. Then, XT100 was added to the rapid mixer cup, and the mixture was rapidly mixed at 2250 rpm for 4 minutes. Then, Baymod rubber material was added, and the mixture was rapidly mixed at 2000 rpm for 4 minutes. Allow the material to cool for 5 minutes, then rapidly mix at 2250 rpm for 4 minutes. Allow the material to cool for a few more minutes, then rapidly mix at 2000 rpm for 4 minutes. Next, add CuNap, PAM 200, HDK H18, and ESS50F, and rapidly mix the mixture at 2000 rpm for 4 minutes, then cool in a freezer for about 5 minutes. Next, add PW80, SB, and SL300, and rapidly mix the mixture at 2000 rpm for 4 minutes. After mixing, cool the material in a freezer for about 5 minutes. Then add methyl methacrylate, followed by rapid mixing at 2250 rpm for 1 minute. After rapid mixing, degas the final binder resin mixture by covering the mixing cup with a polypropylene cap containing a vent, and mix at a high shear rate of 1500 rpm for 2 minutes under reduced pressure of 0.68 psi (about 35 torr). The prepared adhesive resin mixture was individually loaded into 10 sections of a 10:1 dual syringe dispenser, with an accelerator of the acrylic adhesive trade name “3M SCOTCH-WELD DP8810NS” (3M Corporation, St. Paul, Minnesota) used in 1 section of the dispenser in each case.
[0122]
[0123] Exemplary Example A
[0124] Exemplary Example A was prepared by combining the components shown in Table 4 in a polypropylene MAX 600 DAC cup (Sonchong Corporation). Each of the material components in each group was rapidly mixed at 1750 rpm for 4 minutes, unless otherwise specified. First, hydroxyethyl methacrylate (HEMA), methacrylic acid, benzyltributylammonium chloride (N+CL-), and methoxyethylhydroquinone (MEHQ) were combined and rapidly mixed at 1500 rpm for 4 minutes using a DAC 400.2 VAC (Sonchong Corporation). Then, the solid EPX-IEM material was melted in an oven at 66°C (150°F), and the molten material was added to the rapid mixer cup, and the resulting material was rapidly mixed at 2250 rpm for 4 minutes. Then, XT100 was added to the rapid mixer cup, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. Next, the Baymod rubber material was added, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. The material was allowed to cool for 5 minutes, and then rapidly mixed at 1900 rpm for 4 minutes. Then repeat the rapid mixing procedure. Next, add CuNap, PAM 200, HDK H18, and ESS50F, and rapidly mix the mixture at 1900 rpm for 4 minutes. Add PW80, CB, and SL300 and rapidly mix the mixture at 1900 rpm for 4 minutes. Then degas the final adhesive resin mixture by covering the mixing cup with a polypropylene cap containing a vent hole and mixing under high shear at a reduced pressure of 0.68 psi (approximately 35 torr). The prepared adhesive resin mixtures are individually loaded into 10 sections of a 10:1 dual-syringe dispenser, using an accelerator, trade name “3M SCOTCH-WELD DP8810NS” acrylic adhesive (3M Company), in each case, on one section of the dispenser.
[0125]
[0126] Exemplary Example B
[0127] Exemplary Example B was prepared by combining the components shown in Table 5 in the following steps using a polypropylene MAX 600 DAC cup (Sonchon Corporation). Each of the material components was rapidly mixed as described. First, hydroxyethyl methacrylate (HEMA), methacrylic acid, lauryl methacrylate, isobornyl methacrylate, benzyltributylammonium chloride (N+CL-), and methoxyethylhydroquinone (MEHQ) were combined and rapidly mixed at 1500 rpm for 4 minutes using a DAC 400.2 VAC (Sonchon Corporation, Landrum, South Carolina). The solid EPX-IEM material was then melted in an oven at 71°C (160°F) for several hours, and the molten material was added to the rapid mixer cup, and the resulting material was rapidly mixed at 2250 rpm for 4 minutes. Then, XT100 was added to the rapid mixer cup, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. Baymod rubber material was then added, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. Allow the material to cool for 5 minutes, then rapidly mix at 2250 rpm for 4 minutes. Allow the material to cool for a few more minutes, then rapidly mix at 1900 rpm for 4 minutes. Next, add CuNap, PAM 200, HDK H18, and ESS50F, and rapidly mix the mixture at 1900 rpm for 4 minutes. Next, add PW80, SB, and SL300, and rapidly mix the mixture at 1900 rpm for 4 minutes. After mixing, cool the material in a freezer for 5 minutes. Then add methyl methacrylate, followed by rapid mixing at 2250 rpm for 1 minute. After rapid mixing, degas the final binder resin mixture by covering the mixing cup with a polypropylene cap containing vent holes, and then mix under high shear at a reduced pressure of 0.68 psi (approximately 35 Torr) for 2 minutes. The prepared adhesive resin mixture was individually loaded into 10 sections of a 10:1 dual syringe dispenser, with an accelerator of the acrylic adhesive trade name “3M SCOTCH-WELD DP8810NS” (3M Corporation, St. Paul, Minnesota) used in 1 section of the dispenser in each case.
[0128]
[0129] result
[0130] The Tg of each cured adhesive was measured using the tanδ peak from DMA analysis, and the Tg data are listed in Table 6.
[0131]
[0132] The resulting mixed adhesive was used to prepare overlap shear test specimens on various substrates at various temperatures. All adhesives used for the overlap shear test were prepared by dispensing approximately 0.3 g of the adhesive resin mixture and accelerator resin via a static mixing tip. The overlap shear tests were conducted on untreated plastic and metal specimens as described in the above overlap shear tests in Examples 1, Exemplary Example A (Ill. Ex. A), and Exemplary Example B (Ill. Ex. B), and the results are presented in Tables 7 and 8 below.
[0133]
[0134]
[0135] As described in the heat / humidity cycling test, heat / humidity cycling data of Example 1 and Exemplary Examples A and B were collected on aluminum and nylon 6,6 substrates, and the results were the percentage of bond strength retained, which are recorded in Table 9 below.
[0136]
[0137] As described in the water immersion overlap shear test, data from two weeks of 60°C water immersion tests on glass fiber epoxy resin substrates for Examples 1, Exemplary Examples A and B, and DP8407 were collected, and the results were the percentage of bond strength retained, which are recorded in Table 10 below.
[0138]
[0139] A two-week mud-covering agent test was conducted on Example 1 and exemplary Examples A and B. The results are shown in Table 11 below.
[0140]
[0141] The foregoing description, given to enable those skilled in the art to practice this disclosure protected by the claims, should not be construed as a limitation on the scope of this disclosure, which is defined by the claims and all their equivalents.
Claims
1. A composition comprising: Based on the total weight of the acrylic functional compounds in the composition, at least 1% by weight and less than 20% by weight of acrylic monomers containing carboxylic acid groups; At least one of alkyl acrylates or alkyl methacrylates; Acrylic monomers containing hydroxyl groups; and Based on the total weight of the acrylic functional compounds in the composition, 20% to 35% by weight of a compound comprising a divalent segment L and at least two X groups, wherein the divalent segment L is represented by the following formula: L Each of the two-valent segments L is directly bonded to: i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group. ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or iii) secondary N atoms, which are directly bonded to another divalent chain segment L or X group; and tertiary N atoms, which are directly bonded to p other divalent chain segments L and (2-p) X groups, where p is 0, 1 or 2. Each R 1 Independently representing an alkylene group having 1 to 4 carbon atoms, provided that the R 1 At least some of the groups are -CH2-CH2-CH2-CH2-, where each n independently represents a positive integer, and where each X group is independently represented by the following formula: CH2=C(R)-C(O)-OVWC(O)- Each R is independently hydrogen or methyl, and each W is independently O, S, or NR. 2 , where R 2 It is hydrogen or an alkyl group having up to 4 carbon atoms, and wherein each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group.
2. The composition of claim 1, wherein the acrylic monomer containing the hydroxyl group is present in an amount of at least 5% by weight and at most 25% by weight, based on the total weight of the acrylic functional compound in the composition.
3. The composition according to claim 1, wherein at least one of the alkyl acrylate or alkyl methacrylate is methyl methacrylate.
4. The composition of claim 1, wherein the composition comprises at least 20% by weight and at most 50% by weight of methyl methacrylate based on the total weight of the acrylic functional compounds in the composition.
5. The composition of claim 1, wherein, based on the total weight of the acrylic functional compounds in the composition, the acrylic monomer comprising the carboxylic acid group is present in an amount of at least 5% by weight and at most 19% by weight.
6. The composition of claim 1, wherein the composition is free of lauryl methacrylate or contains up to 1% lauryl methacrylate based on the total weight of the acrylic functional compounds in the composition.
7. The composition according to claim 1, wherein the composition further comprises a toughening agent.
8. The composition according to claim 1, wherein the composition further comprises a filler.
9. The composition according to any one of claims 1 to 8, wherein the composition further comprises a free radical initiator.
10. The composition according to any one of claims 1 to 8, wherein the composition is packaged as a first part of a two-part adhesive composition, wherein the second part comprises a free radical initiator.
11. An adhesive comprising the composition according to any one of claims 1 to 8, the composition being at least partially cured with a free radical initiator, wherein the adhesive composition has a glass transition temperature in the range of 90°C to 130°C.
12. An adhesive comprising the composition according to any one of claims 1 to 8, the composition being at least partially cured with a free radical initiator, wherein the composition has an elongation in the range of 30% to 80%.
13. An article of manufacture, said article of manufacture bonded using a composition according to any one of claims 1 to 8, said composition being at least partially cured with a free radical initiator, said article of manufacture comprising at least one of polyamide, acrylonitrile butadiene styrene, poly(meth)acrylate or polyvinyl chloride.
14. A method for preparing an adhesive article comprising a first substrate and a second substrate, the method comprising: Combining the composition according to any one of claims 1 to 8 with a free radical initiator to provide an adhesive composition; The adhesive composition is applied to at least one of the first substrate or the second substrate; The adhesive composition is used to adhere the first substrate and the second substrate; as well as The adhesive composition is allowed to cure at least partially in order to prepare the adhesive article.
15. The method of claim 14, wherein at least one of the first substrate or the second substrate comprises at least one of polyamide, acrylonitrile butadiene styrene, poly(methyl methacrylate) or polyvinyl chloride.
Citation Information
Patent Citations
adhesives for dentin
DE4219700A1
1,2,6-Thiadiazine-3,5-dione-1,1 dioxides and their use
EP0059451B1
Two-part adhesive
JP2016155892A
Method for making silicone hydrogel contact lenses
US20120139138A1
Urea-based pressure sensitive adhesives
US20160137893A1